A most peculiar book: the inherent strangeness of the Bible - Swenson, Kristin M. (Oxford University Press, 2021)
"I have a confession to make. But I'm worried that what you, an intelligent and discerning reader, will hear is not exactly what I mean. Then you'll close this book and put it right back on the shelf. Yet what I want to tell you-and the fact that it feels like a confession-is what drives this entire project. So, here it is: I love the Bible. That statement gives me the willies. It's something millions of Americans would nod right along with because it sounds so simple to understand. But my love for the Bible is not a tacit acceptance of everything in it as truths that demand immediate application. Not hardly. It's not of the swept-off-my-feet, love-at-first-sight variety, but rather more like the complicated love that might develop after decades in a marriage, an arranged marriage. I grew up with the Bible in an open-minded, garden variety Protestant congregation. And I've come to love the Bible for all sorts of reasons, including some of the same reasons that can make it problematic and exasperating"